Pengaruh Penerapan Buerger Allen Exercise Terhadap Sirkulasi Ekstremitas Bawah DM Tipe 2 - Kurniasari, Septi; Antika, Desi (CV. Rayyan Dwi Bharata, 2024)
Diabetes Mellitus, especially type 2, is very common in Indonesia. This is a serious problem since it can lead to consequences, such as reduced blood supply to the legs. A particular leg exercise called the Buerger Allen Exercise is intended to treat circulation issues in the lower limbs. The purpose of this study was to look into how Buerger Allen Exercise affected the circulation in the lower extremities of people with type 2 diabetes. A quasi-experimental design with a one group pre-post test structure was used, along with a quantitative analytical method. A technique known as purposive sampling was used to choose 27 participants. The bivariate analysis method used was the Paired Sample T-Test. The results of the study showed that Buerger Allen Exercise had a significant impact on circulation in the lower extremities in those with type 2 diabetes.